MOHEs engagement programme with national representatives towards the internationalization of HEIs - Mimi Rabita, Abd Wahit (UMPSA, 2024)
KUALA LUMPUR, 5 February 2024 - The programme, involving the Minister of Higher Education (MOHE) and representatives of foreign countries, took place during the Networking Luncheon with Diplomatic Missions in Malaysia at the Wyndham Grand Bangsar, Kuala Lumpur.